Heating duration effects on post-fire structural steel mechanical properties - Gordon, James A.; Bozeman, Scott C.; Fischer, Erica C.; Isgor, O. Burkan; Tucker, Julie D. (Fire safety journal, 2023)
Post-fire mechanical assessment of steel structures is challenging due to the changes in mechanical properties from the heating and cooling phases of a fire. While the effects of cooling rate and temperature of exposure have been researched in depth, the effects of heating duration are not comprehensive. This paper investigates the effects of heating duration on post-fire A572 Gr. 50 steel mechanical properties over a temperature range of 500–800 °C for durations of 0.5 and 2.0 h. Specimens are subjected to tensile testing in accordance with ASTM A370, Vickers microhardness testing, and optical microscopy. The findings suggest that heating duration has an influence on the post-fire mechanical properties of steel at elevated temperatures (700, 800 °C). At these temperature exposures, retention of yield stress, retention of ultimate stress, and microhardness all decrease. Members subjected to 700 °C for 0.5 h have more retention in yield stress and microhardness compared to those exposed for 2.0 h, while the 800 °C conditions show little difference in mechanical properties between exposure times. The results of this study show that the duration of fire exposure is an important factor when estimating the mechanical properties of fire-exposed steels, in addition to the temperature and cooling rate.